Mineral composition of five improved varieties of cassava - Adeniji, T.A.; Sanni, Lateef O.; Barimalaa, I.S.; Hart, A.D. (2007)
Five new cassava mosaic disease resistant (CMD) varieties released to farmers in Nigeria were evaluated for mineral composition. Results show that TME 419 differed significantly (p<0.05) from other varieties in calcium (900ìg/ g) and manganese (32.3ìg/g) content. The hybrid check (TMS 30572) and TMS 98/0505 were significantly different (p<0.05) from other varieties in magnesium (1300ìg/g) and potassium (3900ìg/g), respectively. TMS 97/2205 differed significantly (p<0.05) from other varieties in phosphorus (1200ìg/g) and sodium (63.7ìg/g). Data also revealed that TMS 98/0581 was significantly different (p<0.05) from other varieties in iron (184.2ìg/g) while TMS 98/0510 differed significantly (p<0.05) from other varieties both in copper (10.9ìg/g) and zinc (8.5ìg/g). Chipping and grating had no significant effect (p>0.05) on calcium, sodium, copper, and zinc content of cassava flour. However, treatment effect was obvious in other minerals, chipped having a significant difference (p<0.05) in magnesium, potassium and manganese contents compared to grated samples. Conversely, grated samples differed significantly (p<0.05) in phosphorus and iron compared to chipped samples. Estimated daily recommended dietary allowances (RDA) from major minerals found in CMD varieties show that calcium, potassium, phosphorus and copper contributions to RDA ranged from 17.5-22.5%, 13.8-20.7%, 32.1-42.9%, and 127.8-302.8% in both adult males and females, respectively if 250g flour is eaten daily. The highest level of magnesium contribution (81.3% and 104.8%) to RDA was found in TMS 30572 for adult males and females, respectively, from 250 g flour. TMS 98/0581 was highest in iron contribution to RDA with 575.6% and 255.8% for adult males and females, respectively, provided 250 g flour is eaten. TMS 98/0510 had the highest level of contribution to RDA, 19.3% for adult males, while 26.6% is accruable to adult female, provided 250 g flour is consumed. New cassava varieties may constitute important raw materials in the food industries based on their nutritional composition.